Enhancing Quality Control in the Mix Design of High-Strength Concrete Using a Capacity-Based Approach - Dhiman Basu; Sheikh Mayesser Mushtaq; Shivani Sharma; Sandesh Tripathi (International Journal of Concrete Structures and Materials)
Abstract The mix design of concrete is an important aspect that affects its strength and durability. This paper aims to revisit the existing mix design method given in IS 10262:2019 through a capacity-based approach. The approach involves identifying the possible failure modes in concrete and eliminating the undesirable ones leading to significant reduction in dispersion. This is accomplished by utilizing coarse aggregates that meet a specific minimum strength requirement or threshold (e.g., ~ 77 MPa for M95 grade of concrete), which is determined through a priori estimating the cohesion and friction angle of the concrete. The methodology to estimate the cohesion and friction angle from a single unconfined compression test is proposed based on the Mohr–Coulomb theory and using the orientation of failure plane of fractured specimen as a supplemental information from the same experiment. This paper also offers a simple and approximate test procedure to estimate the aggregate's compressive strength (~ 106 MPa in this mix design) reasonably which is essential for the capacity-based mix design. An experimental programme is also carried out to design the concrete mix using the proposed capacity-based approach. The results indicate that M95 concrete is achieved with a low standard deviation and coefficient of variation (~ 3%), falling in class of excellent quality control as per ACI 214R-11. This quality control is crucial in seismic structural design as variations in concrete strength is likely to negate the underlying principle of strong column–weak beam philosophy resulting in the triggering of undesirable shear modes of failure.